Transcriptional, growth factors, components of the AKT/mTOR signaling pathway, receptors and ligands of programmed cell death expression in melanoma - K. V. Nikulnikov; V. A. Bogdanova; L. V. Spirina; S. Yu. Chizhevskaya; I. V. Kondakova; E. L. Choynzonov; V. I. Chernov (Успехи молекулярной онкологии)
Introduction. Melanoma is the most dangerous neoplasm of the skin, characterized by a malignant and aggressive course. Transcriptional and growth factors, components of the AKT/mTOR signaling pathway, receptors and ligands of programmed cell death are involved in significant processes of oncogenesis.Aim. To study the expression of components of the AKT/mTOR (mTOR – mammalian target of rapamycin) signaling pathway, transcription and growth factors, expression of AMPK, LC3B, programmed cell death 1 (PD-1), programmed death-ligand 1 PD-L1 and programmed death-ligand 2 (PD-L2) in skin and mucosal tumor tissues.Materials and methods. The study included 21 patients with a verified diagnosis of melanoma of the skin of various localizations and mucous membranes of the nasal cavity T1a–4bN0M0 (I–IV stages) and 18 patients with basal cell carcinoma of the skin of various localizations T1–4N0M0 (I–VIA stages), aged 45 to 72 years old, who were treated in the department of head and neck tumors of the Cancer Research Institute, Tomsk National Research Medical Center. The presence of tumor ulceration was determined by microscopy and registration of the true absence of the epidermis over the tumor or due to traumatization of the epidermis. Expression of components of the AKT/mTOR signaling pathway, transcription and growth factors, expression of AMPK, LC3B, PD-1, PD-L1 and PD-L2 in the tumor tissue was determined by real-time polymerase chain reaction.Results. An increase in the expression of 70 S6 kinase and VHL was found in melanoma tissues compared to basal cell carcinoma. At the same time, the presence of signs of ulceration was associated with a low level of c-RAF, nuclear factor kappa B (NF-kB) p50 and hypoxia-inducible factor 1 (HIF-1) matrix RNA (mRNA) against the background of an increase in the expression of the hypoxia-inducible factor 2 (HIF-2) transcription factor. The study of the molecular features of neoplasms in relation to the tumor thickness according to Breslow revealed the contribution of transcription and growth factors, the intensity of intracellular signaling processes, modification of the microenvironment, autophagy and neoangiogenesis.Conclusion. The molecular and biological features of melanomas associated with invasive tumor growth have been identified. An increase in the expression of 70 S6 kinase and VHL are characteristic of a malignant skin tumor. The presence of signs of ulceration and tumor invasion were associated with a change in the transcriptional characteristics of factors with the induction of key markers, oncogenesis, which contributes to the formation of the invasive potential of the tumor.